Katekese Virtual kepada Korban Bencana Alam di Masa Pandemi Menurut Model Berteologi Kosuke Koyama - Antonius Denny Firmanto; Mathias Jebaru Adon (UIN Sunan Gunung Djati Bandung, 2021)
Currently, Indonesia is entering difficult phases because the Indonesian nation is not only dealing with the storm of the Covid-19 pandemic but also natural disasters. This disaster brought a traumatic experience for the victims. Healing for victims can indeed be done with a psychological approach, but strengthening faith is no less important. Based on this, the focus of research studies is on the role of religious institutions, particularly the Church, in handling victims of natural disasters. The role of the Church is seen in catechesis. In catechesis, the Church teaches the values of the gospel and confirms the faith of the people that the suffering experienced is not a curse from God. During a pandemic, catechetical work can be done by utilizing virtual spaces such as social media content. Social media is a means of proclaiming the faith that is easily accessible by the people. This kind of catechetical and theological method was initiated by Kosuke Koyama. According to Koyama, the right catechesis model must start from the concrete problems of the people. Based on this, this research study uses the literature study method. Literary sources were researched and analyzed so that a catechetical model was found that was appropriate to the social context of the Indonesian people who were being hit by natural disasters.